The response of precipitation and surface hydrology to tropical macro-climate forcing in Colombia - Marín, Saul, author; Ramírez, Jorge, A., advisor; Pielke, Roger A., Sr., committee member; Salas, José D., committee member; Smith, Freeman M. committee member; Wohl, Ellen, committee member (Colorado State University. Libraries, 2004)
Regional and local weather and climate behaviors are strongly affected by macroclimate phenomena that perturb the general atmospheric circulation. In tropical regions, and specifically tropical South America, weather and climate are affected by such factors as the meridional oscillation of the Inter-tropical Convergence Zone, the Pacific and Atlantic oceans, the Amazon basin, and the Andes Mountains, among others. Interactions between atmosphere and oceans in this region produce the so-called El Niño/Southern Oscillation (ENSO) phenomenon, which is recognized as the dominant mode of the inter-annual climate variability in the Tropical Pacific. Colombia is among the South American countries that experience large climate anomalies because of ENSO. In fact, ENSO variability explains about 50% of the observed variance of Colombian hydrology beyond the annual cycle when a linear relationship is assumed. However, the hydrologic response in Colombia to a particular ENSO event is highly complex and nonlinear. In order to describe this complex, non-linear hydro-climatic response to large scale atmospheric forcing in Colombia, a coupled atmospheric-land surface hydrology modeling approach was implemented whose main components are Colorado State University's Regional Atmospheric Modeling System (RAMS) and the Swedish Hydrologiska Byråns Vattenbalansavdelning Hydrologic Modeling System (HBV-HMS). RAMS is used in a two-nested grid domain for seasonal simulations and a four-nested grid domain for daily simulations. Seasonal simulations emphasize the annual cycle at regional scales, focusing on the spatial and temporal distribution of the hydro-climatic response to ENSO forcing at monthly time scales. Daily simulations focus on describing the diurnal cycle for specific watersheds. The HBV-HMS is implemented for a set of specific watersheds and used to examine watershed response at daily time scales. Results showed that the spatial distribution of precipitation in Colombia is highly dependent on the local circulation processes generated by complex interactions between large scale atmospheric forcing and the complex surface features present in the region. Results of the seasonal simulations showed that temperature, pressure, water mixing ratio, relative humidity and wind velocity distributions are very well represented. On the other hand, pronounced differences are observed in the precipitation field, especially in centers of higher precipitation, and an imbalance between mountains and valleys is produced. However, the general pattern of precipitation is good enough as a criterion to qualify areas of deficit or surplus rainfall. Remarkably, results show that the warm phase of ENSO leads to a generalized decrease of precipitation along the Andes ranges and that the low lands of Colombia get more precipitation than during a cold ENSO phase. Similarly, daily simulated fields show a very good agreement with observed values. However, the simulated diurnal cycle of precipitation exhibits a temporal phase lag of several hours. Furthermore, daily simulations tend to underestimate both the total amount of precipitation and the duration of precipitation events. Despite these discrepancies, the results of the coupled modeling effort clearly demonstrated the ability of this approach to capture the non-linear and complex interactions of large-scale atmospheric forcing and local characteristics as indicated by the satisfactory simulation of streamflow responses for a set of small watersheds. Results show the great potential of using this tool for regional climate forecasting for at least one season ahead in Colombia, which is fundamental in water resources planning. The ability to describe appropriately the effects of macroclimatic phenomena and general climatic circulation on the regional and local hydro-climate system of Colombia is important, especially because of the complexity of the processes occurring in this mountainous region, with its local atmospheric circulations and the complex thermally driven circulations. Finally, the feasibility to link the output of the atmospheric modeling system with a hydrologic modeling system shows a great potential for developing operational short-term forecasting essential for an optimal operation of water resources systems.
Keywords: atmosphere; hydrology